Stunting Prevention Based on Local Wisdom in Bantul Regency, Yogyakarta, Indonesia - Rochana Ruliyandari; Fitriana Putri Utami; Helfi Agustin; Ratu Matahari (Social Medicine)
The large number of stunting cases worldwide is a global nutritional issue. Stunting is a problem that needs to be addressed since it can jeopardize future human resources and impact health and even child mortality. The Yogyakarta Special Region in Indonesia has managed to bring down the prevalence rate of stunting to a level below the national average. Bantul, a Yogyakarta regency, has been successful in bucking the trend of stunting cases for three years in a row (2020–2022). To facilitate their eventual implementation in other regions, this report outlines the procedures and initiatives that have been carried out in the Bantul Regency. To investigate the role of stakeholder efforts to expedite stunting reduction, this research used a qualitative study methodology using a case study technique. The following sources were specifically chosen as informants: the head of the Imogiri I and II Public Health Centers; the head of the Imogiri Sub-district; eight village heads in the Imogiri Village; the head of the Imogiri Office of Religious Affairs; and one coordinator of family planning cadres in Imogiri Village. Focus Group Discussions (FGD), in-depth interviews, and document reviews were the methods of data gathering employed in this study. Content analysis techniques were applied to the data. The head of the community health center utilized specific nutritional interventions by creating an innovative program, which provided additional food to toddlers, called Community Feeding Center (CFC), YourPROTEIN, and Alms One Egg Program. Sensitive nutrition intervention must involve cross-sector collaboration and synergy, by prioritizing the local Indonesian culture of gotong royong (community mutual assistance). It is essential to build a mindset in the community that stunting is a health issue, to maximize efforts to lessen stunting. Therefore, ongoing proactive communication interventions, using a variety of channels and approaches, are required at the village level.